2018
DOI: 10.1016/j.neuroimage.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resting state condition on reliability, trait specificity, and network connectivity of brain function measured with arterial spin labeled perfusion MRI

Abstract: Resting state fMRI (rs-fMRI) provides imaging biomarkers of task-independent brain function that can be associated with clinical variables or modulated by interventions such as behavioral training or pharmacological manipulations. These biomarkers include time-averaged regional brain function as manifested by regional cerebral blood flow (CBF) measured using arterial spin labeled (ASL) perfusion MRI and correlated temporal fluctuations of function across brain networks with either ASL or blood oxygenation leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Some studies have used LST-theory to disentangle state and trait components using biological data, such as cortisol based on multi-state single-trait models from two parallel measures (Hellhammer et al, 2007) and electroencephalogram data (Hagemann, Hewig, Seifert, Naumann, & Bartussek, 2005) applying a true (error-free) intraindividual change model that considers latent state changes between occasions. LST modeling was also applied to investigate trait specificity and network connectivity reliability on resting state functional magnetic resonance imaging condition, for different task conditions (Li et al, 2018). These previous studies showed innovative ways of dealing with repeated (discrete) measures across time, but the LST approach remains uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used LST-theory to disentangle state and trait components using biological data, such as cortisol based on multi-state single-trait models from two parallel measures (Hellhammer et al, 2007) and electroencephalogram data (Hagemann, Hewig, Seifert, Naumann, & Bartussek, 2005) applying a true (error-free) intraindividual change model that considers latent state changes between occasions. LST modeling was also applied to investigate trait specificity and network connectivity reliability on resting state functional magnetic resonance imaging condition, for different task conditions (Li et al, 2018). These previous studies showed innovative ways of dealing with repeated (discrete) measures across time, but the LST approach remains uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were instructed to close their eyes and relax to minimize unwanted brain activations during all ASL scans. 12 We also acquired separately a pre-saturated (T sat ÂŒ 4s) proton-density weighted (PD-w) reference scan with vesselsuppression with regular sampling and parallelimaging acceleration only (R ÂŒ 2.5 acceleration factor in both phase and slice dimensions) for coil sensitivity and fully-relaxed magnetization (M 0 ) estimation. This was acquired with the same imaging parameters and system adjustments in 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to stay awake during the acquisition, silent, with closed eyes, to avoid an increase in CBF due to visual stimulation ( Moreton et al, 2016 ; Li et al, 2018 ). Also, they were asked to breathe calmly because it has been reported that respiratory challenges that require the patient to make ventilatory effort result in motion artifacts ( Moreton et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%